Diasporical Experiences of Gauri in Jhumpa Lahiri’s The Lowland - Sri, V.Aparna; Ramya, S. (International Journal of Psychosocial Rehabilitation, 2020)
This paper tends to analyze the experiences of gauri in Jhumpa lahari’s The Lowland. Loneliness is camouflaged throughout the novel. The main protagonists discussed in this paper are Gauri and Bela. It explores how one’s past affects oneself as well the offspring. In this novel, it analyses why and how Gauri is affected and how she affects Bela. How they both try to create an identity of their own. In a new place, perspective of a woman is different from that of a man. The author has talked about the irony of freedom through Gauri. It is a clash between freedom from social stigma or from the imaginary bonds from mind, heart and soul. The author has juxtaposed India and Rhodeisland in the lowland.